2009
DOI: 10.1158/0008-5472.can-08-2826
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Regulatory Dendritic Cells Inhibit CD8+ T Cell Function via l-Arginine Metabolism

Abstract: Dendritic cells (DC) have a critical effect on the outcome of adaptive immune responses against growing tumors. Whereas it is generally assumed that the presence of phenotypically mature DCs should promote protective antitumor immunity, evidence to the contrary does exist. We describe here a novel mechanism by which tumor-infiltrating dendritic cells (TIDC) actively contribute to the suppression of protective CD8

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
201
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(215 citation statements)
references
References 44 publications
10
201
2
2
Order By: Relevance
“…The authors also distinguished this population of DCs from myeloid derived suppressor cells (MDSCs), a distinctive cell population known for its immune suppressive activity in cancer models. 32 In our study, we found that combinatorial therapy correlated with a significantly lower frequency of CD11b + CD11 c + TIDCs. Further gating on MHCII expression revealed a significant reduction in CD11b + CD11 c + MHCII hi TIDCs in all treated groups relative to control.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The authors also distinguished this population of DCs from myeloid derived suppressor cells (MDSCs), a distinctive cell population known for its immune suppressive activity in cancer models. 32 In our study, we found that combinatorial therapy correlated with a significantly lower frequency of CD11b + CD11 c + TIDCs. Further gating on MHCII expression revealed a significant reduction in CD11b + CD11 c + MHCII hi TIDCs in all treated groups relative to control.…”
Section: Discussionsupporting
confidence: 52%
“…A prior study has shown that TIDCs with high MHCII expression (CD11b + CD11 c + MHCII hi ) may inhibit CD8 + T cell function in the setting of murine mammary carcinoma. 32 In our study, brains of untreated mice had a significantly greater percentage (10.64% ± 2.23) of tumor-infiltrating CD11b + CD11 c + MHCII hi cells than brains of mice receiving anti-PD-1 antibody alone (1.984% ± 0.48; p = 0.0054), anti-TIGIT antibody alone (4.148% ± 2.04; p = 0.0399), or both checkpoint inhibitors (0.908% ± 0.35; p = 0.0020). No significant difference was observed across the three treatment groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, murine lung cancer could "educate" cDCs to differentiate into CD11c low CD11b high Ia low regDCs that inhibit T cell response, as was reported by Liu et al using the freshly isolated tumor cells to mimic the tumor microenvironment in DC co-culture studies [13]. Norian [14]. An altered cell fate program characterized by minimal T cell expansion, impaired IFN-γ production, and anergy is resulted from the stimulation of naïve T cells with these regDCs.…”
Section: Introduction: Regulatory Dendritic Cells In Cancermentioning
confidence: 85%
“…Expression of inhibitory molecules on regDCs, like programmed cell death 1 ligand 1 (PD-L1) and PD-L2, is another pathway responsible for regDC-mediated inhibition of anti-tumor immunity. Although these and other mechanisms of immunosuppression induced by regDCs have been reported [14,[30][31][32][33][34], it is still unknown which tumor-derived factors or local microenvironmental stimuli are responsible for polarization of cDCs into regDCs in different model systems and for differential expression of a variety of immunosuppressive molecules in regDCs in different conditions. Interestingly, Kuang et al have recently reported that hyaluronan fragments derived from cancer cells drove human monocytes to become tolerogenic semimature DCs, which triggered rapid down-regulation of CD3-ε and TCR-α/β and subsequent apoptosis in autologous T cells [35].…”
Section: Immunosuppressive and Tolerogenic Activity Of Regulatory Denmentioning
confidence: 99%
See 1 more Smart Citation